1990
DOI: 10.1111/j.1440-1630.1990.tb01230.x
|View full text |Cite
|
Sign up to set email alerts
|

The Perceived Status of Occupational Therapy: Myth Versus Reality

Abstract: A survey of 136 Australian occupational therapists explored their perception of their autonomy and status, through questions concerning role definition; peer network and peer review; professional association and industrial affiliation; skills and procedures characteristic of the profession; views on others' perception of their role; credentials to practise; salary and years of practice. The authors conclude that the profession has a high opinion of its status and autonomy, a belief that it has a unique set of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

1994
1994
2000
2000

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 6 publications
0
7
1
Order By: Relevance
“…The extent to which others determine the role of the occupational therapist will influence their practice in the healthcare team. This contrasted with the findings of Graham and Timewell (1990) from a small sample of occupational therapists in Australia who felt that their roles were most frequently set by their own conception, and that only infrequently were they dictated to by a superior occupational therapist, other professionals or administrators. The extent to which therapists feel they are able to determine the nature of their own practice will affect their confidence and clarity about their role.…”
Section: Other Factors Affecting Team Functioningcontrasting
confidence: 80%
See 1 more Smart Citation
“…The extent to which others determine the role of the occupational therapist will influence their practice in the healthcare team. This contrasted with the findings of Graham and Timewell (1990) from a small sample of occupational therapists in Australia who felt that their roles were most frequently set by their own conception, and that only infrequently were they dictated to by a superior occupational therapist, other professionals or administrators. The extent to which therapists feel they are able to determine the nature of their own practice will affect their confidence and clarity about their role.…”
Section: Other Factors Affecting Team Functioningcontrasting
confidence: 80%
“…It may be expected that therapists with greater role confidence and clarity will be more comfortable in a team. Graham and Timewell (1990) concluded that there is a false consciousness among occupational therapists in relation to their perceived status within the healthcare system. They suggested that the external indicator of prestige, namely salary, did not reflect a profession with high status.…”
Section: Other Factors Affecting Team Functioningmentioning
confidence: 99%
“…Occupational therapists have searched for status based on the accumulation of 'ticks' against a notional check list of attributes and have assumed that the position of occupational therapy would change as a function of changes in attributes (Webster, 1986;Wallis, 1987a,b;West, 1989;Do Rozario & Ross, 1991). This has not been the case (Graham & Timewell, 1990).…”
Section: Implications Of Adherence To Trait Theorymentioning
confidence: 88%
“…In a study of the perceived status of occupational therapy among occupational therapists, Graham and Timewell (1990) found that respondents had a high opinion of the status and autonomy of the discipline. The researchers argued that this self image may not be well founded.…”
Section: Implications Of Adherence To Trait Theorymentioning
confidence: 99%
See 1 more Smart Citation